A linear inertial piezoelectric actuator using a single bimorph vibrator. (9th October 2019) - Zhang, En; Hu, Yili; Bao, Huilu; Li, Jianping; Ma, Jijie; Wen, Jianming
Abstract: A linear inertial piezoelectric actuator using a single bimorph vibrator clamped by asymmetrical fixed beam structure is proposed in this paper to achieve extremely simple structure and high stability. It adopted one vibrator to produce the inertial impact force, which is beneficial to simplify the overall architecture. A dynamic model, based on the stiffness-damping vibration model and LuGre friction model, is established to predict the motion of the actuator by Matlab/Simulink. An experimental system is built to test its performance. Experimental results indicate that the stable minimum displacement is 1.9 μ m and the maximum repeat error rate reaches 1.1% under a square wave signal of 15 V, 2 Hz with no-load. When the load is 420 g, the minimum displacement is 0.6 μ m under 100 V and 2 Hz. Compared with similar actuators, the proposed actuator achieves much higher stable linear motion with a larger stroke and without drawback.